The absence of prophylactic antibiotics administration and the surgical site infections rate in Mohs micrographic surgery - Pradita, Riva Ambardina; Wibawa, Larisa Paramitha (UI Scholars Hub, 2020)
Background: The use of prophylactic antibiotics in dermatologic surgery, particularly in Mohs micrographic surgery (MMS), remains a gray area. Despite the low rate of surgical site infection (SSI), SSI can result in some significant morbidities. Thus, numerous dermatologists keep administering prophylactic antibiotics in MMS. Method: A search was conducted to identify clinically significant topics followed by literature review through the main available medical literature database. The three selected studies that met the inclusion and exclusion criteria were then critically assessed for their validity, importance, and applicability using the guidance from Centre for Evidence-Based Medicine for Critical Appraisal of Prognostic Studies. Results: Three articles showed a low SSI rate with a narrow confidence interval (CI): 0.91% (95% CI: 0.38%– 1.45%), 0.7% (95% CI: 0.21%–1.19%), and 0.72% (95%CI: 0.5%–0.9%). Conclusion: Based on the available studies, we conclude that the absence of prophylactic antibiotics is not related to the SSI incidence.